Mario Osorio Marques: a desecrator´s pedagogisms of death (Revista Contexto & Educação, 2025)
This article reflects on the contributions of the humanist Mario Osorio Marques in the context of education. He is an original thinker who is still little known in academia. The thematization of his life is based on the experience of one of his former students, in consultation with his works and other theoretical contributions, resulting in bibliographic research of a qualitative and poetic nature. His epistemic stance of thinking about educational problems made him break geographical boundaries. Among his achievements is the creation of FAFI (Faculty of Philosophy, Sciences and Letters) in 1957, today the Regional University of the Northwest of the State of Rio Grande do Sul - UNIJUÍ and, later, he was the idealizer in opening the Postgraduate Program in Educational Sciences - PPGEC/Unijuí. Mario Osorio understood like few others the importance of the University as an environment for the formation and development of humanities, using pillars such as research, reading and writing. More than just an act of learning, reading and writing, for him, are acts of resistance. He left much more than a living legacy of understanding the University and of secular education that does not give in to the impoverishment imposed by the rational, fragmentary and transmissive logic to which we were and continue to be exposed. He left an example of epistemological persistence, demonstrating that reading, writing and knowing are pillars of human emancipation, producers of the world, generators of consciousness and living energy that impel and challenge us to be all too human in our ethical-formative untimeliness.
Keywords: University; Human Formation; Mario Osorio Marques